Efficient multi-receiver signcryption scheme based on ring signature. (2nd March 2023) - Su, Pengfei; Israr, Muhammad; Ma, Ruijiang; Xie, Yong
With the development of society, the problem of the disclosure of the identity information of whistleblowers has become more and more prominent, resulting in few people willing to become whistleblowers. Anonymous signcryption schemes can be used to solve the problems faced by whistleblowers, and the multi-receiver signcryption in the form of one-to-many communication is more suitable. Existing related schemes all use bilinear or exponential operations, which are impractical in terms of whistleblower application because of complexity. An efficient multi-receiver signcryption scheme based on ring signature is proposed in this paper. It adopts the method of hiding the sender's identity in the set of identities trusted by the receivers to realise the anonymity of the sender and the reliability of the sender. A strict security proof shows that the proposed scheme is secure. Complexity analysis and comparison show that the efficiency advantage of the proposed scheme is obvious.